The evolution of bilateral relations between the US and Iran during Iran-Iraq war (1980-1988) - Pavliuk Olesia Igorivna (Studia Humanitatis, 2016)
The author explores the evolution of the methods of the US influence to the Islamic Republic of Iran during the Gulf War 1980-1988. Algerian agreement in 1981 did not become the basis for the settlement of US-Iranian relations in the early 1980s, because the Iranian government continued to sponsor terroristic radical extremist organizations in the Middle East, thereby causing harm to the US interests. Therefore, the administration of R. Reagan prolongs the effect of emergency economic measures against Iran and introduces additional sanctions. After reviewing its neutrality, the US prefers a more predictable Iraq in the Iran-Iraq war and announces Operation Staunch, aimed to cooperate with other countries to refuse to supply weapons in Iran. Promoting greater weakening of rivals of each other was considered as the greatest interest of the US in the war where no country could become the leader in the region and prevent the spread of the American influence in the Middle East.